Trauma, Memory and Witnessing in Seneca’s Moral Epistles - Várhelyi, Zsuzsanna (Acta Classica Universitatis Scientiarum Debreceniensis, 2026)
Spurred by the recent identification of fragments from Seneca the Elder’s historical work, ab initio bellorum civilium, this paper investigates how Seneca the Younger navigated Roman memory culture in light of the enduring, intergenerational trauma of selective imperial silencing.  It examines the complications heirs faced when preserving banned texts in an atmosphere of imperial censorship in a twist on traditional pietas that required one to preserve their father's memory. Against this historical background, and given emperors’ claim to absolute exemplarity while alive and the speedy reversal of those honors upon their deaths, Seneca’s Moral Epistles can be seen as a strategic attempt to reclaim some control over his own posthumous reception, entrusting the image of his life and of his death to a future community of like-minded individuals.